Avascular Bone Necrosis in Pediatric Patients with Sickle Cell Disease in Basrah, Iraq - Wadha Abdullah Hamood; Meaad Kadhum Hassan; Wissam Jabar Yesser (Journal of Applied Hematology, 2024)
BACKGROUND: Avascular necrosis (AVN) is regarded as a manifestation of severe sickle cell disease (SCD), with the femoral head being the most affected. OBJECTIVES: The main objectives of this study were to look for the frequency of AVN in pediatric patients with SCD, evaluate the clinical pattern and severity of AVN, and study the possible risk factors associated with AVN. MATERIALS AND METHODS: A cross-sectional study has been conducted on SCD patients, aged 6–18 years, who visited the Basrah Center for Hereditary Blood Diseases from the first of February 2021 to August 2021. Patients were screened for AVN by hip plain radiography and magnetic resonance imaging. The modified Ficat-Arlet staging system was used to classify different stages of AVN. RESULTS: The total number of screened patients was 291; 193 (66.3%) had sickle cell anemia, 71 (24.4%) with S/β0 thalassemia, 21 (7.2%) with S/β+ thalassemia, and 6 (2.1%) had S/D disease. Fifty-eight (19.9%) patients were found to have different stages of AVN; 7 (12.1%) were asymptomatic and 51 (87.9%) were symptomatic. The logistic regression analysis has revealed that frequent vaso-occlusive crises requiring hospitalization (B = 1.576, P = 0.003), acute splenic sequestration crises (B = 1.256, P = 0.003), homozygous sickle hemoglobin genotype (B = −0.208, P = 0.001), and low reticulocyte count (B = 1.452, P = 0.027) are significant variables associated with AVN. CONCLUSION: AVN was reported in a significant percentage of pediatric patients with SCD and was associated with selected indicators of disease severity. Further studies that evaluate the natural history, progress of AVN, and variations in selected variables over time like reticulocytes and the co-inheritance of α-thalassemia are important.